High-entropy oxide thin films based on Al–Cr–Nb–Ta–Ti. (October 2019) - Kirnbauer, Alexander; Spadt, Christoph; Koller, Christian M.; Kolozsvári, Szilard; Mayrhofer, Paul H.
Abstract: Single-phase crystalline (Al, Cr, Nb, Ta, Ti)O2 high-entropy oxide thin films were synthesized at 400 °C by reactive magnetron sputtering of an equimolar Al–Cr–Nb–Ta–Ti-compound target. These show similar chemistry as well as the same rutile structure, even when varying the relative oxygen flow-rate ratio ( f O2 ) during deposition over a wide range. Upon increasing f O2 from 30 to 80%, their hardness increases from 22 to 24 GPa and their indentation moduli increased from 380 to 410 GPa. The materials stayed single-phase crystalline with the rutile structure during vacuum annealing up to 1200 °C, only their orientation changed from random-like to highly 101-textured. Highlights: Single-phase solid solution oxide independent of oxygen flow rate. High hardness compared to respective ternary oxide coatings. Strong texture of coatings after annealing at 1200 °C.